Mathematical tools in computer graphics with C# implementations - Hardy, Alexandre; Steeb, Willi-Hans. (Singapore : World Scientific, 2008)
Mathematics is vital for an understanding of computer graphics. This volume helps the reader gain such an understanding by presenting all introductory and most advanced topics in the field of computer graphics with mathematical descriptions and derivations. Offering a balance of theory, applications, and code, the underlying numerical methods and algorithms are derived and a large number of examples are given.
Includes bibliographical references and index.
Keywords: Computer graphics -- Mathematics; C# (Computer program language).